The Harmony Of The Ideas Of Michel Montaigne With The Socio-Political And Spiritual Reality In The Era Of Globalization (Texas Journal of Multidisciplinary Studies, 2024)
The article analyzes Michel Montaigne's ideas of moral criteria arising from the characteristics of his time, which measure the morals of any person in the society and guide him to a new way of thinking. Attention is paid to Montaigne's views on human nature, which correspond to the spirit of the new era and to the education of a unique personality in this era. It is known that moral rules are created by people to obey them, but it is noted that cases of going beyond or circumventing them lead people to the abyss.